Sustainability Review 2017 - World Bank (Washington, DC, 2017)
The Sustainability Review 2017 provides insights into World Bank activities undertaken between July 1, 2016, and June 30, 2017, to manage the environmental, social, and economic impacts of internal business operations. The content and data in this document relate to the International Bank of Reconstruction and Development (IBRD) and the International Development Association (IDA), together, the World Bank.